PENGARUH KEDISIPLINAN BELAJAR TERHADAP PRESTASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS VIII DI SMP NEGERI 26 KOTA MALANG - Debby Feramitha; Ika Ratih Sulistiani; Mohammad Eko Nasrulloh (VICRATINA, 2020)
The discipline of learning is one of the factor to improve the chance to get learning achievement. When the achievement was improved, educational goals can be achieved. Identify a significant effect between learning discipline on student achievement is the purpose of this study. This thesis is using quantitative research. Research population consisted of 207 students, then samples were taken using the Slovin formula and producing the sample of 136 out of 207 students. Data collecting procedures is using questionnaire research instruments, interview, and documentation. Data processing in this study uses Simple Linear Regression Analysis with the back up SPSS computer software 20.0 version. Based on data analysis, it can be concluded that there is a positive and significant influence between learning discipline on learning achievement in Islamic religion subjects 8th at Junior High School 26 Malang with an α = 0,00 < 0,05, then H0 is rejected and Ha is accepted.